World Bank Group Engagement in Situations of Fragility, Conflict, and Violence - Independent Evaluation Group (World Bank, Washington, DC, 2016)
The report discusses how challenging it is for the World Bank Group to provide assistance when middle-income countries experience situations of fragility, conflict, and violence. The government may have its own views on how and when to tackle the underlying issues, or may be reluctant to increase its borrowing to correct what may be seen as a localized or temporary problem. Through examining such cases, IEG concluded that the Bank Group’s comparative advantage is supporting countries in tackling long-term development challenges, including early engagement and a sustained presence in conflict-affected areas, as well as continuous dialogue with the parties to violent conflicts, where possible.